Chance involvement in goal scoring in football - an empirical approach - Lames, M. (German Journal of Exercise and Sport Research, 2018)
This study examines the impact of chance in football using the case of goal scoring. For this purpose, chance in goal scoring is defined as goals involving uncontrollable or not planned aspects. "Chance variables" were defined according to the principle of downward estimation, i.e. when one of these variables is involved this is an uncontrollable or not planned aspect of scoring a goal, although chance may also have an impact in instances other than those collected. Six "chance variables" were identified: deflection, rebound, goalkeeper involvement, post/bar hits, long distance shots, and defence involvement. In the 2011/2012 season, the 875 goals in German Bundesliga and the 1056 goals in English Premier League were examined for the presence of these variables. Of the goals examined, 47.0% showed at least one chance variable (deflection: 4.8%; rebound: 9.4%, goalkeeper: 2.5%; post/bar: 5.2%; distance: 13.1%, and defence: 22.5%). The two leagues differed significantly only in the sense of more goalkeeper interventions in the Bundesliga and more distance goals in the Premier League. The rate of chance-goals drops significantly with the number of prior goals in a match (2=17.59; p=0.004). In both leagues, there is no significant correlation between final ranking and the percentage of chance-goals scored or conceded. If one accepts the selected chance variables as indicators of uncontrollable or not planned aspects of scoring, the results of this study can be taken as empirical proof for the existence and widespread prevalence of chance involvement in goal scoring in football with many interesting consequences.